2021
DOI: 10.1126/science.aba0862
|View full text |Cite
|
Sign up to set email alerts
|

Clinically relevant mutations in core metabolic genes confer antibiotic resistance

Abstract: Although metabolism plays an active role in antibiotic lethality, antibiotic resistance is generally associated with drug target modification, enzymatic inactivation, and/or transport rather than metabolic processes. Evolution experiments of Escherichia coli rely on growth-dependent selection, which may provide a limited view of the antibiotic resistance landscape. We sequenced and analyzed E. coli adapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
206
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 251 publications
(225 citation statements)
references
References 57 publications
16
206
0
3
Order By: Relevance
“…Enrichment of translation and ribosomal structure genes (COG J), and energy production genes (COG C) in trimethoprim/sulfonamide group might be due to altered metabolism and changes in energy production leading to bacterial persistence and escape of antibiotic effect [61,62]. Similar findings were recently reported by Lopatkin et al [63] where it was shown that mutations in metabolic genes, in particular, central carbon and energy metabolism genes, lead to the increased antibiotic resistance. Ultimately, GWAS is a promising approach for a systematic innately complex bacterial resistance analysis, which could be applied to better understand the genetics of antibiotic resistance development.…”
Section: Discussionsupporting
confidence: 76%
“…Enrichment of translation and ribosomal structure genes (COG J), and energy production genes (COG C) in trimethoprim/sulfonamide group might be due to altered metabolism and changes in energy production leading to bacterial persistence and escape of antibiotic effect [61,62]. Similar findings were recently reported by Lopatkin et al [63] where it was shown that mutations in metabolic genes, in particular, central carbon and energy metabolism genes, lead to the increased antibiotic resistance. Ultimately, GWAS is a promising approach for a systematic innately complex bacterial resistance analysis, which could be applied to better understand the genetics of antibiotic resistance development.…”
Section: Discussionsupporting
confidence: 76%
“…These changes are evidence of the complementary role of GlpK. Based on this global deregulation, we hypothesize a diversified strategy led by GlpK to overcome antagonism in nutritional competitive scenarios (Figure 6C), supporting the recent ecological concept where new antibiotic resistance strategies point to the importance of mutations in metabolic genes (Lopatkin et al, 2021). First, GlpK causes the induction of sporulation and transcriptional changes in carbon source acquisition genes.…”
Section: Discussionsupporting
confidence: 71%
“…In recent years, advances in laboratory evolution, high-throughput sequencing, and computational biology have greatly expanded the scope of addressable questions in microbiology and the study of antibiotic resistance ( 16 ). For instance, adaptive laboratory evolution can simulate natural selection pressures ( 17 ), allowing researchers to study the emergence of novel antibiotic treatment phenotypes ( 18 ), as well as their relationship to environmental conditions ( 19 ). In many cases, these granular experimental techniques invite complementary computational modeling activities, from mechanistically simulating drug-target binding to predicting complex ecological dynamics, yielding deeper insights into clinical resistance phenomena.…”
Section: Digitalization In Clinical and Research Settingsmentioning
confidence: 99%